PENGARUH KOMPETENSI PROFESIONAL GURU TERHADAP KINERJA MENGAJAR GURU SEKOLAH DASAR - Ida Saidah (Universitas Pendidikan Indonesia, 2021)
This study aims to determine the effect of teacher professional competence on the teaching performance of elementary school teachers in Harjamukti District, Cirebon City. The research approach used is descriptive research with a quantitative approach. The population in the study were elementary school teachers in Harjamukti District, Cirebon City, totaling 586 teachers. The sampling technique used is the Probability Sampling technique through Proportionate Stratified Random Sampling, because the members in the population are heterogeneous or not of the same type so that they are proportionally stratified. The sample is determined as much as 15% of the population. So the calculation is 586 x 15/100 = 87.9 rounded to 88, then the total sample that the researcher will take is 88 teachers and the author only takes 2 teachers from each school. Hypothesis testing uses correlation coefficient analysis, determination analysis, significance level test and simple regression coefficient test. The prerequisite test is the normality test. All calculations were processed using the SPSS (Statistical Package for School Science) program version 25.0 for Windows. The results of data processing obtained from the correlation coefficient value of 0.860, which means that Teacher Professional Competence has a very strong correlation or relationship with Teacher Teaching Performance. The coefficient of determination (KP) is 73.9%, meaning that the Teaching Performance of Teachers is influenced by the Professional Competence of Teachers of 73.9% and the remaining 26.1% is determined by other factors not examined. The results of the regression equation illustrate that there is a dependency between Teacher Teaching Performance on Teacher Professional Competence with the regression equation Ŷ = 15.605 + 0.856????. This means that these results state that for each change in Teacher Professional Competence by one unit, the increase will be followed by an increase in Teacher Teaching Performance by 0.856.